Introduction to the Special Issue on Accounting Academia in Central and Eastern Europe - Catalin Nicolae Albu; Nadia Albu (Journal of Accounting and Management Information Systems (JAMIS), 2015)
Several calls have been made to investigate the processes of change characterizing academia worldwide. In particular, the tension apparent between the 'universal' models (standards, rankings) on the one hand, and the cultural and social features of academia in specific countries on the other hand, was deemed very fruitful to be researched. Most Central and Eastern European (CEE) countries share a communist past and have transitioned toward a market economy, more or less rapidly or successfully. Their academic environment is characterized by common traits, but where apparent, improvements have mostly emerged through sustained individual efforts, rather than through coherent and systematic thinking of education officials. However, many challenges faced by accounting academics affiliated with institutions in CEE countries are similar, and the experience of others may prove very significant. Therefore, we want to give a more coherent perspective on the processes of change and of the evolutions happening at the regional level. The topics proposed for investigation include: the academic environment and the consequences on accounting research; the construction of the accounting academic's identity, and the relationship between accounting education, research, and practice; and accounting education. The aim of this introduction to the special issue is to give an overview of these topics in accounting academia in CEE countries, by mobilizing our own understanding and experience, and the international literature.
Keywords: A23; M41; I23; 650; accounting academia; CEE countries; accounting education and research; academic evaluation